Metode Pembelajaran Pendidikan Islam Berbasis Multikultural Dan Berbasis Peserta Didik - Haq, Vick Ainun; Opstibdawati, Sri (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Education in Indonesia is the spearhead in caring for diversity and the nation's next generation, therefore it is necessary to cultivate the character of students in line with national values, diversity, multiculturalism and pluralism. Thus, these values ​​are also inseparable from what is contained in religious teachings, especially in Islam, which has been explained by the Qur'an and Hadith. In writing this article aims to describe the application of multicultural-based and student-based educational learning, with a focus on Islamic views and learning methodologies carried out by teachers to students in the classroom. While the method in this study uses a literature review, where the author collects data from various sources according to the research topic. The results of this study indicate that the multicultural education method puts forward aspects of togetherness to create a sense of mutual respect for each other's differences, while character-based education of students in order to form a moral character, love for the homeland, discipline and responsibility.